Fortification of rice crisps with fish protein hydrolysate (Decapterus sp.) for iron deficiency prevention - Daysita, Lulu Eki; Laily, Noer; Wijayanti, Sri Peni; Giarni, Reni; Widjayanti, Retno Dumilah Esti (Journal of Food Technology Research, 2025)
Iron deficiency remains one of the most widespread nutritional challenges globally, often addressed through dietary supplementation and food fortification. However, the limited bioavailability of iron in common food sources often hampers these efforts. Recent interest has grown in the use of protein hydrolysates to enhance iron absorption due to their abundance of low-molecular-weight peptides. This study explored the fortification of rice crisps with fish protein hydrolysate derived from Decapterus sp, aiming to improve the nutritional quality of a familiar snack and its potential to help reduce iron deficiency risk. The hydrolysate was characterized by its peptide molecular weight distribution, which showed a predominance of peptides under 15 kDa. Tyrosine emerged as the most abundant free amino acid, comprising 40.75% of the total amino acid content in the hydrolysate. The digestibility of the fish protein hydrolysate (DPH) was measured at 31.78%, with a protein concentration of 121 ppm and an iron-binding activity of 0.025%. Among all formulations, the sample containing 15% hydrolysate (F3) was most favored in sensory tests, balancing nutritional enrichment with consumer acceptability. These findings suggest that incorporating fish protein hydrolysates into popular food products may offer a promising, sustainable approach to combat iron deficiency, particularly among vulnerable populations such as children and women of reproductive age.